Pengaruh Komunikasi dan Disiplin Kerja Terhadap Kinerja Karyawan: Study Case Anigre Kitchen - Nurul Sukma Lestari; Novita Indah Mulyaningrum; Albert Christminho Kesuma; Achmad Hidayat Sutawijaya (Universitas Mercu Buana, 2022)
Communication within an organization/company can have a major impact on the performance and viability of the company, this affects things like innovation, safety and operational improvement. Likewise with work discipline, every organization requires work discipline because it is important for company operations to follow the rules that have been set. The main purpose of this study is to determine whether there is an influence between communication and work discipline on employee performance at Anigre Kitchen. The research method used is qualitative research, using a saturated sample of 17 Anigre kitchen employees. Data were obtained through questionnaires, interviews and literature studies. The results of the study partially show that communication and work discipline have a positive and significant effect on employee performance. While the results simultaneously show that the variables of communication and work discipline together have a significant effect on employee performance. The R square value of employee performance is influenced by independent variables, namely communication and work discipline, obtained from the results of the determination test, while the rest is explained by variables outside the study. It is recommended for companies to improve communication and work discipline so that employee performance can continue to improve and be maintained for the company's sustainability. For further research, it is recommended to use a larger sample size and choose hotels from various local and international brands to see wider results